Beyond the Jam: Women’s Experiences and Career Pathways in Game Development - Almeida, Luciana; Figueiredo, Mayara; Batista, Any; de Souza, Cleidson (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc_estendido.2026.20129, 2026)
This thesis examines women’s experiences in game jams and how these events influence their professional trajectories. Using a multiphase mixed-methods design, four empirical studies combined descriptive quantitative analyses with inductive qualitative coding. By profiling women game jam participants, systematizing their recurrent difficulties into a taxonomy, identifying gender-specific difficulties, and analyzing how game jams influence career pathways, this thesis reveals these events as inherently ambivalent spaces. On the one hand, game jams foster learning, experimentation, and professional exploration; on the other hand, they reproduce exclusionary dynamics present in the game industry. The findings further indicate that women mobilize coping strategies that may alleviate immediate barriers but often shift the responsibility for inclusion to the individual level, i.e., to themseleves. Moreover, game jams emerge not only as entry points, but also as mechanisms of retention, motivation, and, in some cases, disengagement from the industry. Taken together, these results reposition game jams as critical sites for advancing women’s inclusion in the game industry.